Negotiation of Spirituality and Technocracy: The Future of Islamic Education Management in the Era of Society 5.0 - Asep Rohani (Indonesian Journal of Multidisciplinary Science, 2026)
This article aims to analyze the relationship between spirituality and technology in the transformation of Islamic Education Management in the era of Society 5.0 and formulate an adaptive, humanistic, and sustainable paradigm of Islamic education management. This research uses a qualitative approach with a conceptual-critical type of research through the library research method. Data was obtained from various internationally and nationally reputable scientific literature in the last five years relevant to the theme of Society 5.0, digital transformation of education, spirituality, and Islamic education. The results of the study show that digital transformation in Islamic education cannot be understood solely as technological modernization but must be balanced with the strengthening of ethical values, spirituality, and educational humanism. Spirituality has a strategic position as an ethical foundation in directing the use of technology to remain oriented towards the formation of human beings, strengthening manners, and building the character of students. Based on the results of the analysis, this study offers a paradigm of the Spiritual-Technological Islamic Educational Management Framework that integrates spiritual governance, ethical technology, humanistic leadership, and digital educational ecosystem as an alternative model for future Islamic education management. This research contributes to expanding the discourse of Islamic education management through futuristic and interdisciplinary approaches and provides a conceptual foundation for the development of Islamic educational institutions that are adaptive to technological developments without losing their moral and spiritual identity.